Linking molecular targets to hypertrophic cardiomyopathy using genome-edited human induced pluripotent stem cell cardiomyocytes - Bodbin, S.E. (2022)
Hypertrophic cardiomyopathy (HCM) is the most common cardiomyopathy, estimated to affect 1:250 people, resulting in impaired cardiac function due to thickening of the left ventricle. Once disregarded as genomic junk, long non-coding ribonucleic acids (lncRNA) have emerged as key regulators of human disease, including cardiovascular disorders. Work prior to this thesis developed an hiPSC- CM model of HCM, introducing the pathological R453C mutation into the MYH7 sarcomeric gene. RNA sequencing on the lines of the of model uncovered four lncRNAs that may be involved in the progression or prevention of HCM.